Analysis Of The Effect Of Competency On Audit Quality - Gde Deny LARASDIPUTRA; Ni Putu Riski MARTINI (Indonesia Strategic Sustainability, 2020)
This study discusses the influence of Auditor Competence on Audit Quality in the Influence of Computer Assisted Audit Techniques (TABK). This research was conducted at a public accounting firm in Bali. The research time is 2020. The population of this research is 13 Public Accounting Firms (KAP) in Bali with 76 auditors. The sampling technique used in this research is purposive sampling technique. Based on the results of the analysis, it can be concluded that: Auditor competence has a positive effect on audit quality and computer-assisted audit techniques are able to moderate the relationship between auditor competence and quality.